Underwater Restocking Innovation by the Marine and Fisheries Office of East Java Province to Enhance Fisheries Productivity and Community Economy - Tarisyah Diva Anggraini; Vidya Imanuari Pertiwi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The marine biodiversity of Indonesia is exceptionally diverse. It is no surprise that this attracts foreign countries to commit illegal activities, specifically illegal fishing. Illegal fishing is an unlawful practice that threatens the sustainability of Indonesia's marine resources. It causes a decline in fish populations within territorial waters, which in turn impacts the economy of fishing communities. This study aims to evaluate the extent to which the Underwater Restocking innovation contributes to restoring damaged marine ecosystems and increasing fishery yields. The method employed in this research is qualitative, using a case study approach at the Department of Marine Affairs and Fisheries of East Java Province. Data was collected through interviews, documents, and relevant reports. The findings indicate that although the effectiveness of the Underwater Restocking innovation still requires further evaluation, it has shown positive impacts by helping increase fishermen's productivity by approximately 60%. The author believes that this innovation represents a strategic step in restoring marine ecosystems and improving the economy of the community, provided it is implemented consistently. Keywords: Department of Marine Affairs and Fisheries of East Java Province, Illegal Fishing, Innovation, Underwater Restocking.